Ročno ali digitalno? Obdelava lesa v OŠ - Golob, Miha (Pedagoška perspektiva, 2025)
This article examines the possibilities of integrating modern forms of wood processing into elementary school technical education. It focuses on combining manual work with digital processing using a basic CNC milling machine. The article emphasizes that even simple technical solutions can create a learning experience that bridges the gap between analog and digital methods while improving understanding of technological processes. The hybrid approach supports the development of motor skills, spatial awareness, and technical literacy, helping students grasp the difference between traditional and modern production techniques. It also presents feasible lesson structures suitable for limited resources and highlights the motivational value of such instruction. The proposed approach is applicable within regular lessons or as part of a technical day or extracurricular activity. The article draws on domestic sources and good practices, encouraging schools to introduce technologies that have so far been typical mainly of higher levels of education.
Keywords: CNC technology; CNC tehnologija; les; manual processing; osnovna šola; primary school; ročna obdelava; technical education; tehnično izobraževanje; wood